Homeland - Warner, Rachel (Wayland Hove, 1993)
The book "Homeland" by Rachel Warner and Kaye Stearman, published in 1993 by Wayland. This 48-page hardcover is part of the "Human Rights" series and is suitable for middle primary to junior secondary students. The book explores the concept of a homeland$1 (Ba place where individuals feel they belong$1 (Band examines various situations where people's rights to their homelands are challenged. Through case studies, it discusses issues such as divided, lost, invaded, controlled, and conflicting homelands, highlighting the struggles of different groups around the world. The aim is to provide starting points for debates on key human rights issues.s